Admission Neutrophil-Lymphocyte Ratio (NLR) Predicts Survival in Patients with Extensive Burns. Issue 3 (May 2021) - Hu, Lunyang; Wang, Baoli; Hong, Yonggang; Xu, Long; Jiang, Yong; Wang, Chen; Zhu, Banghui; Yu, Qing; Hou, Wenjia; Chen, Zhengli; Zhu, Feng; Wu, Guosheng; et al.
Highlights: The prognostic value of NLR in extensive burn patients was investigated. The univariate and multivariate regression analysis were used to discuss the relationship of clinical variables and outcomes. The NLR cut-off values at the first 3 days of hospitalization were calculated by the ROC analysis. Abstract: Background: Extensive burns is one of the most common severe injuries, with a high annual death rate. Previous studies showed that the neutrophil to lymphocyte ratio (NLR) is a prognostic factor for some inflammatory diseases. However, until now, no study has evaluated the clinical prognostic value of NLR in extensively burned patients. The aim of this study was to investigate the prognostic value of NLR in this medical condition to provide clinical guidance. Methods: 271 patients diagnosed with extensive burns were analysed retrospectively between 2005 and 2018 in the Department of Burn Surgery of Changhai Hospital. NLR cut-off values at the first 3 days of hospitalization were calculated by the ROC analysis. Results: Of the 271 patients in this study, the majority (82.3%) were injured by flame. The median total body surface area (TBSA) was 55% (IQR, 40% to 85%) and the median full thickness burn (FTB) was 20% (IQR, 3%–44%). The patients' NLR declined within the first 3 days after admission, and we found that NLR was negatively correlated with the ventilator-free days at day 28 (r = -0.127, P = 0.048). In a multivariate logistic regression analysis, higher admission NLR was independently predictive of higher mortality. According to the ROC curve, the best cut-off values for day 1 (or admission day), day 2 and day 3 NLR were 14, 13 and 7.5, respectively. We then performed a survival analysis, finding that those NLR above the cut-off point had decreased overall survival compared to those with NLR below the cut-off point (p = 0.023, 0.045 and 0.019 for day 1, 2, and 3, respectively). Conclusions: NLR continuously decreased in the first 3 days of hospitalization. Admission NLR above 14 is associated with a decreased survival in patients with extensive burns. These findings demonstrate that NLR has prognostic value in these patients.